Significance of the parkin and PINK1 gene in Jordanian families with incidences of young-onset and juvenile parkinsonism - Nusier Mohamad K; Horany Khalid; Zayyad Hiba; Nilsen Gina L; Stormyr Alice; Steinkjer Stina; Myhre Ronny; Klungland Helge (BMC Neurology, 2008)
Abstract Background Parkinson's disease is a progressive neurodegenerative disorder, where most cases are sporadic with a late onset. In rare incidences familial forms of early-onset parkinsonism occur, and when recessively inherited, cases are often explained by mutations in either the parkin (PARK2) or PINK1 (PARK6) gene or on exceptional occasions the DJ-1 (PARK7) or ATP13A2 (PARK9) gene. Recessively inherited deletions/duplications and point mutations in the parkin gene are the most common cause of early-onset parkinsonism known so far, but in an increasing number of studies, genetic variations in the serine/threonine kinase domain of the PINK1 gene are found to explain early-onset parkinsonism. Methods In this study all families were from a population with a high incidence of consanguinity. We investigated 11 consanguineous families comprising 17 affected with recessively inherited young-onset parkinsonism for mutations both in the parkin and PINK1 gene. Exons and flanking regions were sequenced, and segregation patterns of genetic variation were assessed in members of the respective families. An exon dosage analysis was performed for all exons in both genes. Results In the parkin gene, a three generation family was identified with an exon 4 deletion segregating with disease. Both affected were homozygous for the deletion that segregated on a haplotype that spanned the gene in a haplotype segregation analysis that was performed using additional markers. Exon dosage analysis confirmed the recessive pattern of inheritance with heterozygous deletions segregating in healthy family members. In the PINK1 gene we identified two novel putative pathogenic substitutions, P416R and S419P, located in a conserved motif of the serine/threonine kinase domain. Both substitutions segregated with disease in agreement with a recessive pattern of inheritance within respective families and both were present as homozygous in two affected each. We also discuss common polymorphisms in the two genes found to be co-segregating within families. Conclusion Our results further extend on the involvement of PINK1 mutations in recessive early-onset parkinsonism with clinical features similar to carriers of parkin mutations.